2010
DOI: 10.1097/tp.0b013e3181f2c962
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Outcomes With Machine Perfusion and Longer Pump Times in Kidney Transplantation: A Single-Center, Observational Study

Abstract: Mean cold storage and pump times were 6.6 and 26.7 hr, consistent across immunosuppression protocols. Overall DGF and SGF rates were 4.4% (15/339) and 12.1% (41/339). DGF was equally low for pump time less than 24 vs. more than or equal to 24 hr, 5.2% (6/116) vs. 4.0% (9/223) (P=0.63), with similar results after adjusting for known DGF predictors. A significantly lower first BPAR rate was observed for longer pump time (as a continuous variable) among more immunologically active recipients (those having more ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 48 publications
3
48
2
Order By: Relevance
“…[20][21][22][23][24][25][26][27][28][29] Others studies have suggested that HMP may permit longer CIT without increasing DGF rates. 23,30 The present study supports this concept. Despite the significantly longer CITs in the HMP group, less DGF was experienced than in kidneys stored for shorter periods using SCS.…”
Section: Discussionsupporting
confidence: 80%
“…[20][21][22][23][24][25][26][27][28][29] Others studies have suggested that HMP may permit longer CIT without increasing DGF rates. 23,30 The present study supports this concept. Despite the significantly longer CITs in the HMP group, less DGF was experienced than in kidneys stored for shorter periods using SCS.…”
Section: Discussionsupporting
confidence: 80%
“…From the analysis of the differentially expressed genes in this group, most of these genes were downregulated in the noDGF lo group and were found to be involved in intracellular localization and cellular transport. These gene changes may provide a biological explanation to what has been described in the literature as "slow graft function" (26)(27)(28). Finally, few differentially ex- pressed probe sets were identified between the DGF hi and noDGF hi subgroups, indicating that transcriptionally these two groups of patients are very similar.…”
Section: Continuedmentioning
confidence: 78%
“…All deceased donor organs were cryopreserved using Water's RM3 Renal Preservation Machine with Belzer-MPS Machine Perfusion Solution (Trans-Med Corp., Elk River, MN) (47).…”
Section: Methodsmentioning
confidence: 99%